Early New Ischemic Lesions Located Outside the Initially Affected Vascular Territory Appear More Often in Stroke Patients with Elevated Glycated Hemoglobin (HbA1c) - Braemswig, Tim Bastian; Nolte, Christian H.; Fiebach, Jochen B.; Usnich, Tatiana (Frontiers in Neurology, 2017)
Background: Early new ischemic lesions are common in patients with an acute ischemic stroke. These new ischemic lesions may represent the natural course of the initial stroke or de novo events. Objective: We hypothesized that early new ischemic lesions located outside the initially affected vascular territory would point at de novo events. Therefore, we differentiated new ischemic lesions located outside the initially affected vascular territory from those occurring only inside the initially affected vascular territory to identify risk factors that are associated with de novo events. Methods: Stroke patients underwent three magnetic resonance imaging (MRI) examinations (at 3 Tesla): on admission, on the next day and four to seven days after symptom onset (clinicaltrials.gov : NCT00715533). Diffusion-weighted imaging (DWI) lesions were delineated, co-registered and then analyzed for new hyperintensities on follow-up examinations by raters blinded to clinical details. Patients were classified as having "new distant lesions" if new DWI lesions appeared outside or both outside and inside the initially affected vascular territory or "new local lesions" if they were only inside. Results: 115 patients with early new DWI lesions constitute the study population. Sixteen patients (14%) had new distant lesions and 99 patients (86%) had new local lesions. In comparison between patients with new distant and new local lesions, patients with new distant lesions had significantly more often elevated glycated hemoglobin (HbA1c ≥ 6.5%; p = 0.022). Conclusion: Our data indicate that patients with elevated HbA1c have an increased risk for new, de novo ischemic lesions in the acute phase after an ischemic stroke.